2019
DOI: 10.1111/and.13489
|View full text |Cite
|
Sign up to set email alerts
|

Sperm retrieval from a male with the rare 47, XXYqs variant of Klinefelter syndrome for intracytoplasmic sperm injection: A case report

Abstract: A 27‐year‐old man with nonobstructive azoospermia was diagnosed with Klinefelter syndrome (KS) with a satellite Y chromosome (47, XXYqs) by karyotyping. Genetic analysis revealed azoospermia factor c (AZFc) microdeletion of gr/gr deletion in the Y chromosome. Microdissection testicular sperm extraction (micro‐TESE) was performed in bilateral testes. Very few seminiferous tubules were bilaterally observed, and a minute number of spermatozoa obtained from the left testis were cryopreserved. Histologic examinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although success rates for SSR in KS may be as high as 55% as described above, they may be affected by the degree of genetic abnormality. Enatsu et al ( 32 ) managed to obtain very small numbers of spermatozoa from mTESE for a patient with a 47, XXYqs variant of KS, while another case study revealed Sertoli cell only in a patient with a 47,XY,i(X)(q10) karyotype ( 33 ). Because genetic variants are rare, most of the studies tend to be case reports, so clearly more studies are needed to fully assess the extent of their impact on spermatogenesis.…”
Section: Aneuploidy Ratementioning
confidence: 99%
“…Although success rates for SSR in KS may be as high as 55% as described above, they may be affected by the degree of genetic abnormality. Enatsu et al ( 32 ) managed to obtain very small numbers of spermatozoa from mTESE for a patient with a 47, XXYqs variant of KS, while another case study revealed Sertoli cell only in a patient with a 47,XY,i(X)(q10) karyotype ( 33 ). Because genetic variants are rare, most of the studies tend to be case reports, so clearly more studies are needed to fully assess the extent of their impact on spermatogenesis.…”
Section: Aneuploidy Ratementioning
confidence: 99%